"They created a team of almost entirely the people who work and are like them": A qualitative study of organisational culture and racialised inequalities among healthcare staff. Issue 2 (6th December 2021) - Woodhead, Charlotte; Stoll, Nkasi; Harwood, Hannah; ,; Alexis, Obrey; Hatch, Stephani L.
Abstract: Racially and ethnically minoritised healthcare staff groups disproportionately experience and witness workplace discrimination from patients, colleagues and managers. This is visible in their under‐representation at senior levels and over‐representation in disciplinary proceedings and is associated with adversities such as greater depression, anxiety, somatic symptoms, low job satisfaction and sickness absence. In the UK, little progress has been made despite the implementation of measures to tackle racialised inequities in the health services. So, what is it about the health service organisational context which shapes and maintains such inequities, and what role does discrimination, bullying and harassment play? Drawing on qualitative interviews with 48 healthcare staff in London (UK), we identify how micro‐level bullying, prejudice, discrimination and harassment behaviours, independently and in combination, exploit and maintain meso‐level racialised hierarchies. Within teams, the high diversity–low inclusion dynamic shaped and was perpetuated by in‐ and outgroup inclusion and exclusion processes (including "insidious dismissal") often employing bullying or microaggressions. These were linked to intersecting factors, such as race, ethnicity, migration, language and religion, and could increase segregation. For racially and ethnically minoritised groups, ingroup maintenance, moving teams or leaving were also ways of coping with organisational inequities. We discuss implications for tackling racialised workplace inequities.